Defense engagement since 1900 : global lessons in soft power - Kennedy, Greg (Modern war studies., 2020)
"This is a work of applied military history-where military history is analyzed in order to inform current issues, particularly regarding international security. Defense engagement uses military capabilities to exert what's known as "soft power" (influence) as opposed to "hard power" (military force). As described by Kennedy in his introduction, defense engagement "is a question of looking at the ability of the state's military to move away from thinking of its role as the applicator of force and instead thinking of itself as an applicator of power. ... [T]he purpose of defense engagement is to attempt to tackle the causes of designated security threats and not simply manage their consequences." In recognition of the importance of defense engagement-and with an appreciation of the lack of academic literature addressing defense engagement through historical analysis-this collection offers a number of case studies that explore various dimensions of defense engagement, primarily in the UK, but also including the US, Canada, and Japan. I've included the table of contents under "Additional Comments" below so you can see what case studies are included."--